Diversity of ferns and lycophytes in Brazil - Prado,Jefferson (2015)
Abstract This compilation of ferns and lycophytes in Brazil is an update of the one published in 2010 in Catálogo de Plantas e Fungos do Brasil. The methodology consisted in collecting data from regional checklists, taxonomic revisions, and selected databases. Invited specialists improved the list accessing a website housed at the Jardim Botânico do Rio de Janeiro. The results show 1,253 species: 1,111 of ferns and 142 of lycophytes. This number is 6.5% higher than the previous one (1,176 spp.). The percentage of endemic species decreased from 38.2% to 36.7%. We recognized 36 families and 133 genera (vs. 33 families, 121 genera in 2010). The 10 most diverse families are Pteridaceae (196 spp.), Dryopteridaceae (179), Polypodiaceae (164), Hymenophyllaceae (90), Thelypteridaceae (86), Aspleniaceae (78), Lycopodiaceae (64), Selaginellaceae (55), Anemiaceae (51), and Cyatheaceae (45). The three most diverse genera are still Elaphoglossum (87 spp.), Thelypteris (85), and Asplenium (74). The richest phytogeographic domain continues to be in the Atlantic Rainforest with 883 species which also has the largest number of endemic and threatened species, followed by the Amazon Rainforest (503), Cerrado (269), Pantanal (30), Caatinga (26), and Pampa (eight). Minas Gerais remains as the richest state (657 spp. vs. 580 in 2010).